Examine the Impact of Remote Work on Employee Productivity in MTN - Peter Mucunguzi (Uganda Christian University, 2025)
The shift to working from home introduced by the COVID-19 pandemic has with it new opportunities and challenges to employee productivity, especially in developing nations such as Uganda. While international evidence is in agreement that team working is fruitful with increased flexibility and decreased commuting, these results heavily rely on contextual factors such as information infrastructure, managerial style, and organizational culture. The research examines how team working influences employees' productivity in MTN Uganda, a major telecommunications company. With a theoretical framework placing remote work as the independent variable and worker productivity as the dependent variable, the current study explores how infrastructural limitations, cultural expectations, and management styles intervene between productivity impacts in remote working environments. Employing the mixed-methods approach, quantitative survey and qualitative interviewing are combined to provide rich insights into the degree to which remote work influences the quality, timeliness, and effectiveness of work. The results are to guide organizational practice and national policy that support effective productive remote work arrangements in Uganda's growing digital economy.
Undergraduate